Antimicrobial resistance profile among bacteria isolated from patients presenting with wounds at Kabale Regional Referral Hospital, South western Uganda - Andrew, Baguma; Benson, Musinguzi; Kagirita, Atek Atwiine; Joel, Bazira (Research Square, 2022)
Background: Bacterial Wound infection and antimicrobial resistance remains a public health challenge. The challenge remains worse due to nosocomial bacterial infection often characterized by multidrug resistance. Infected wounds are often associated with delayed epidermal maturation resulting into prolonged hospitalization. Data on profile of clinical significant bacteria and their respective antibiotic drug resistance in Uganda is still limited. In this study we emphasized on phenotypic characterization of bacteria that cause wound infections at Kabale Regional Hospital (KRRH) and determining the respective antimicrobial susceptibility profiles. Methods: Between June 2016 – to June 2017 a total of 276 Pus specimens were collected from patients at KRRH and analyzed for bacterial infection by standard bacterial cultures techniques. Pus specimens were all from wounds (surgical and non-surgical). Antibiotic susceptibility testing was performed and reported based on CLSI guidelines. Results One-hundred and ninety-five specimens were positive following bacterial culture (70.7%). Staphylococcus aureus and Escherichia coli were the most frequently isolated bacteria. Antibiotic drug resistance testing revealed that 68% of S. aureus isolates were Methicillin resistant. For Escherichia coli isolates, 73% were ciprofloxacin and levofloxacin resistant while resistance to Imipenem was common among Klebsiella sp. Conclusions: Wound infection is mainly caused by gram negative bacteria particularly, Escherichia coli , Klebsiella spp., Proteus spp., and Pseudomonas spp. G positive cocci particularly S. aureus is also an important pathogen among other implicated gram positive cocci. There are high levels of multi - antimicrobial resistance among both Gram negative and Gram positive bacteria.